Autoimmune nodopathy with anti-contactin 1 antibody characterized by cerebellar dysarthria: a case report and literature review - Chen, Jiajie; Liu, Lingchun; Zhu, Hongyan; Han, Jinming; Li, Rong; Gong, Xiarong; Fu, Hao; Long, Jingjing; Li, Haixia; Meng, Qiang (Frontiers in Immunology, 2024)
Background: Autoimmune nodopathy (AN) has emerged as a novel diagnostic category pathologically different from classical chronic inflammatory demyelinating polyneuropathy. Clinical manifestations of AN include sensory or motor neuropathies, sensory ataxia, tremor and cranial nerve involvement. AN with serum positive contactin-1 (CNTN1) antibody usually cause demyelination of the peripheral nerve.In this study, we reported a rare case of AN with CNTN1 antibodies characterized by the presence of CNTN1 antibodies in both serum and cerebrospinal fluid, which is associated with cerebellar dysarthria.A 25-year-old man admitted to our hospital due to progressive dysarthria with limb tremor. Initially, the patient was diagnosed as peripheral neuropathy in a local hospital. Three years later, he was admitted to our hospital due to dysarthria, obvious limb tremor and limb weakness. At that time, he was diagnosed as spinocerebellar ataxia. Eight years later, the patient visited our hospital for the second time because of dysarthria (typical cerebellar dysarthria, i.e., tremor, loud voice, stress and interrupted articulation) and progressive limb weakness, accompanied by muscle atrophy of distal lower limbs. Magnetic resonance imaging (MRI), nerve conduction studies (NCS), autoimmune antibody tests were performed.The results of NCS suggested severe demyelination and even axonal damage of the peripheral nerves. MRI scans revealed diffuse thickening of bilateral cervical nerve roots, lumbosacral nerve roots, cauda equina nerve and multiple intercostal nerve root sheath cysts. Furthermore, anti-CNTN1 antibody titer was 1:10 in the cerebrospinal fluid (CSF) and 1:100 in the serum. After one round of rituximab treatment, the patient showed significant improvement in limb weakness and dysarthria, and the CSF antibodies turned negative.Apart from peripheral neuropathies, cerebellar dysarthria (central nervous system involvement) should not be ignored in AN patients with CNTN1 antibodies.